A heterometallic (Fe6Na8) cage-like silsesquioxane: synthesis, structure, spin glass behavior and high catalytic activity. Issue 53 (16th May 2016) - Bilyachenko, Alexey N.; Levitsky, Mikhail M.; Yalymov, Alexey I.; Korlyukov, Alexander A.; Vologzhanina, Anna V.; Kozlov, Yuriy N.; Shul'pina, Lidia S.; Nesterov, Dmytro S.; Pombeiro, Armando J. L.; Lamaty, Frédéric; Bantreil, Xavier; Fetre, Amandine; et al.
Abstract : The exotic "Asian Lantern" heterometallic cage silsesquioxane [(PhSiO1.5 )20 (FeO1.5 )6 (NaO0.5 )8 ( n -BuOH)9.6 (C7 H8 )] (I ) was obtained and characterized by X-ray diffraction, EXAFS, topological analyses and DFT calculation. Abstract : The exotic "Asian Lantern" heterometallic cage silsesquioxane [(PhSiO1.5 )20 (FeO1.5 )6 (NaO0.5 )8 ( n -BuOH)9.6 (C7 H8 )] (I ) was obtained and characterized by X-ray diffraction, EXAFS, topological analyses and DFT calculation. The magnetic property investigations revealed that it shows an unusual spin glass-like behavior induced by a particular triangular arrangement of Fe(iii ) ions. Cyclohexane and other alkanes as well as benzene can be oxidized to the corresponding alkyl hydroperoxides and phenol, respectively, by hydrogen peroxide in air in the presence of catalytic amounts of complexI and nitric acid. TheI -catalyzed reaction of cyclohexane, c -C6 H12, with H2 16 O2 in an atmosphere of 18 O2 gave a mixture of labeled and non-labeled cyclohexyl hydroperoxides, c -C6 H11 – 16 O– 16 OH and c -C6 H11 – 18 O– 18 OH, respectively, with an 18 O incorporation level of ca. 12%. CompoundI also revealed high efficiency in the oxidative amidation of alcohols into amides: in the presence of complexI, only 500 ppm of iron was allowed to reach TON and TOF values of 1660 and 92 h −1 .